Theological Reflections on Psalm 22: From King David to the Crucified Christ - Tanasyah, Yusak; Repi, Robby Robert; Halawa, Maju (RERUM: Journal of Biblical Practice, 2024)
The phrase "My God, my God, why have you forsaken me?" is one of the most poignant and widely recognized lines in the Bible, and it carries profound significance within both Christian and Jewish traditions. This statement is found in Psalm 22, a psalm attributed to King David. Understanding its context within Psalm 22 sheds light on its meaning and significance. From a Christian perspective, the words of Psalm 22:1 take on added significance in light of their connection to the crucifixion of Jesus Christ. According to the Gospels of Matthew and Mark, Jesus quotes Psalm 22:1 while hanging on the cross, thereby identifying himself with the suffering described in the Psalm. This connection between Psalm 22 and the crucifixion underscores the idea that Jesus, in his humanity, experienced the depths of human suffering and anguish. For Christians, Jesus' cry of abandonment on the cross is not merely an expression of personal agony but also a reflection of his role as the sacrificial Lamb of God who takes upon himself the sins of humanity. In this sense, Jesus' cry echoes the suffering of all humanity and serves as a reminder of God's redemptive love and ultimate victory over sin and death. Psalm 22 captures the profound tension between despair and trust, lament and hope. It serves as a powerful expression of human suffering and a reminder of God's faithfulness, culminating in its connection to the crucifixion of Jesus Christ and the hope of redemption for all humanity.